Effects of radiative and microphysical processes on simulated warm and transition season Arctic stratus - Harrington, Jerry Youngblood, author (Colorado State University. Libraries, 1997)
A cloud-resolving model (CRM) version of RAMS, coupled to explicit bin resolving microphysics and a new two-stream radiative transfer code is used to study various aspects of Arctic stratus clouds (ASC). The two-stream radiative transfer model is coupled in a consistent fashion to the bulk microphysical parameterization of Walko et al. (1995), an explicit liquid bin microphysical model (e.g., Feingold et al. 1996a) and a mixed-phase rnicrophysical model (Reisin et al., 1996). These models are used to study both warm (summer) season and transition (fall and spring) season ASC. Equations are developed for the inclusion of the radiative term in the drop growth equation and the effect is studied in a trajectory parcel model (TPM) and the CRM. Arctic stratus simulated with the new CRM framework compared well with the observations of Curry (1986). Along with CCN concentrations, it is shown that drop distribution shape and optical property methods strongly impact cloud evolution through their effect on the radiative properties. Broader cloud top distributions lead to clouds with more shallow depths and circulation strengths as more shortwave radiation is absorbed while the opposite occurs for narrow distribution functions. Radiative-cloud interactions using mean effective radii are shown to be problematic, while conserving re and N of the distribution function (as per Hu and Stamnes, 1993) produces similar cloud evolution as compared to detailed computations. Radiative effects on drop vapor deopsition growth can produce drizzle about 30 minutes earlier and is strongly dependent upon cloud top residence time of the parcels. The same set of trajectories assists drizzle production in the radiation and no-radiation cases. Not only is the growth of larger drops enhanced by the radiative effect, but drops with r < 10µm are caused to evaporate; the effects together constitute a method of spectral broadening at cloud top. Simulations with the CRM show a smaller impact of the radiative influence; this is attributed to the spurious production of cloud top supersaturations by Eulerian models (Stevens et al., 1996a). Simulations of transition season ASC shows that boundary layer stability is strongly dependent upon ice processes, illustrating that the rapid reduction in fall stratus cloud cover may be forced, in part, by microphysical processes. Cloud stability is shown to be strongly dependent upon the cloud temperature, ice concentration, precipitation rate and the indirect effects of ice crystals on cloud top radiative cooling while ice aggregation has a weak effect. Transitions from predominately mixed to stable boundary layers occur and are a function of ice sublimation and precipitation; ice habit strongly constrains the effect. Frequently observed autumnal stable layers may be formed in this fashion. A new method of multiple cloud layer formation is discussed and occurs through the rapid loss of ice from the upper cloud layer, which moistens and cools (sublimation and radiation) the lower layers causing droplet activation.
October 17, 1997.
Also issued as author's dissertation (Ph.D.) -- Colorado State University, 1997.
Keywords: Clouds -- Arctic regions -- Observations; Stratus -- Arctic regions -- Observations; Radiative transfer